1997
DOI: 10.1007/s004250050143
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular communication in plants: electrical stimulation of proteinase inhibitor gene expression in tomato

Abstract: Tomato (Lycopersicon esculentum L.) plants accumulate proteinase inhibitor ( pin) mRNA in response to various stimuli in leaves distant from those treated. Most earlier work suggests that the intercellular wound signals are chemical; we have tried to determine whether electrical or hydraulic signals can also evoke systemic pin expression. We used a mild¯ame to evoke a hydraulic signal and its local electrical aftermath, the variation potential (VP), and an electric stimulus to trigger an action potential. Unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…First, it was shown in several studies that local damage induced changes in stem or leaf thickness that reflected hydraulic wave propagation through the plant. 4,47,53,60,61 Changes in thickness started before the electrical reaction was initiated 4,40,47,51 thus supporting their key role in VP induction. Additionally, artificially increasing xylem hydraulic pressure in the positive direction 7,49,53 induces electrical reactions that are similar to VP.…”
Section: Mechanism Of Variation Potential Propagationmentioning
confidence: 85%
“…First, it was shown in several studies that local damage induced changes in stem or leaf thickness that reflected hydraulic wave propagation through the plant. 4,47,53,60,61 Changes in thickness started before the electrical reaction was initiated 4,40,47,51 thus supporting their key role in VP induction. Additionally, artificially increasing xylem hydraulic pressure in the positive direction 7,49,53 induces electrical reactions that are similar to VP.…”
Section: Mechanism Of Variation Potential Propagationmentioning
confidence: 85%
“…Several studies have found that systemic leaves orthostichous to the wounded leaf accumulate markedly higher levels of PI transcripts and activity than do nonorthostichous leaves, suggesting that the signal is transported by the vascular system (Jones et al, 1993;Orians et al, 2000;Schittko and Baldwin, 2003;Orians, 2005). The involvement of electric and hydraulic signals in mediating the systemic responses has also been proposed Stankovic and Davies, 1997). More importantly, an elegant genetic study strongly argues that JA plays important roles in mediating systemic PI response: either JA or a JA-elicited mobile signal is responsible for systemic PI induction (Li et al, 2002).…”
Section: Mobile Signals and Defense Response Activation In Systemic Tmentioning
confidence: 99%
“…Electrical waves that propagate from the point of injury through the tissue are more likely early and fast signals (Maffei et al, 2007b). Such signals are indeed able to trigger defenses, for example, the up-regulation of proteinase inhibitor genes (Wildon et al, 1992;Stankovic and Davies, 1997;Herde et al, 1998), a response obviously following wounding (Graham et al, 1986). Recently, action potentials in plants have been correlated with defense responses upon herbivore attack (Maffei et al, 2004) and they also have been demonstrated to be released by various compounds (e.g.…”
Section: Wounding As Signal?mentioning
confidence: 99%